1979
DOI: 10.1177/00220345790580120201
|View full text |Cite
|
Sign up to set email alerts
|

A Further Assessment of Predictors of the Child's Behavior in Dental Treatment

Abstract: The child's disruptiveness during dental treatment was related modestly to his age as well as his state, trait, and dental anxiety. In three samples comprising 132 experienced and 49 inexperienced pedodontic patients, the child's behavior during treatment could not be predicted from any aspect of maternal anxiety -- trait, state, or dental. Previous conceptions of maternal influence on the child's dental anxiety should be re-evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
2
11
1
2
Order By: Relevance
“…Previous literature on the effect of anxiety on child's behavior in the dental setting is controversial. The results of the present and previous studies indicate that trait anxiety is not necessarily associated with behavioral problems in the dental setting (16,17). These findings suggest that the nature of this association is complex.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Previous literature on the effect of anxiety on child's behavior in the dental setting is controversial. The results of the present and previous studies indicate that trait anxiety is not necessarily associated with behavioral problems in the dental setting (16,17). These findings suggest that the nature of this association is complex.…”
Section: Discussionsupporting
confidence: 48%
“…Alwin et al (16) found no difference in general anxiety between the groups of cooperative and uncooperative patients. However, Klorman et al (17) found that the patient's trait anxiety was correlated with uncooperativeness in two studies of their three studies, but did not predict behavior profile scores in any sample. The present study was designed to explore the possible correlations between maternal emotional intelligence (EQ) and parenting style with child trait anxiety and child behavior in the dental setting as a stressful condition.…”
Section: Introductionmentioning
confidence: 90%
“…Esta escala permite diferentes formas de utilização. No presente estudo solicitava-se ao médico dentista um julgamento global do comportamento da criança, obtendo-se, assim, uma avaliação holística do seu comportamento em setting de consulta (Klorman, Michael, Hilpert, & Sveen, 1979 de animais em diferentes situações relacionadas com a saúde oral. Os desenhos são apresentados à criança seguindo a ordem numérica e ela é encorajada a contar uma história sobre cada um: "Conta-me, o que está a acontecer no desenho...".…”
Section: Escala De Avaliação Do Comportamento Da Criança Durante O Trunclassified
“…The sensitivity of the picture test has been questioned because the majority of children score zero. [2][3][4] The differences noted in this controlled trial must therefore be interpreted with caution. Furthermore, the intervention may inadvertently have an association with the outcome measure because both the intervention and outcome measure used pictorial methods.…”
Section: Commentarymentioning
confidence: 99%